Differentiating science instruction and assessment for learners with special needs, K-8 - Finson, Kevin D.; Ormsbee, Christine K.; Jensen, Mary M. (Thousand Oaks, California Corwin, 2011)
"This timely, practical guidebook bridges the gap between science and special education by giving teachers strategies and tools that strengthen science learning for all students"-- Publisher.
"This book provides classroom-tested guidelines and suggestions that can be made to science activities and assessments so that they can be differentiated for students with special needs. Included in the book are examples of "original" science activities and assessments and their revised versions as per the guidelines suggested in the book. Each of the national-level science education standards documents (The National Science Education Standards from the National Research Council, the Benchmarks for Scientific Literacy: Project 2061 from the American Association for the Advancement of Science, and the National Science Teachers Association Pathways and Scope, Sequence and Coordination) emphasize that science instruction must be adequately and appropriately provided to all students. Similarly, federal and state legislation (NCLB) has mandated that students in special education be provided with appropriate science instruction and that necessary accommodations be made to further this objective. The classroom teacher is often left to his/her own devices with respect to determining how this can be accomplished. This book is a tool these teachers can use for guidance in this endeavor"--Publisher.
Introduction -- Collaborating to teach students with mild/moderate disabilities in the inclusive classroom -- Addressing specific learning difficulties -- Suggestions for revising science activities and assessments -- Revising science activities -- Revising science assessments -- Developing and using rubrics to evaluate student performance -- Resource: Science literacy, standards, and state goals.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching (Elementary); Science -- Study and teaching (Middle school); Learning disabled children -- Education (Elementary); Learning disabled children -- Education (Middle school); Individualized instruction; Inclusive education